METAVERSE AND ENTREPRENEURSHIP: NEW BUSINESS OPPORTUNITIES IN THE VIRTUAL WORLD - Sandy Tya; Nong Chai; Napat Chai (Journal of Social Entrepreneurship and Creative Technology, 2025)
The emergence of the metaverse has opened up new possibilities for businesses, entrepreneurs, and consumers, reshaping the way industries operate and interact with their audiences. As the virtual world expands, new business opportunities have emerged, allowing entrepreneurs to create innovative products, services, and experiences in entirely digital spaces. However, the potential of the metaverse for entrepreneurship remains underexplored. This research aims to examine how the metaverse offers new business opportunities and challenges for entrepreneurs in various sectors. The study utilizes a qualitative research design, conducting in-depth interviews with entrepreneurs and industry experts who are actively engaging with the metaverse. Data was gathered through semi-structured interviews and analyzed thematically to identify key trends, business models, and challenges faced by startups in virtual environments. The findings reveal that the metaverse provides entrepreneurs with access to a global market, greater consumer engagement, and new forms of monetization through virtual goods and services. However, challenges such as technical barriers, user adoption, and regulatory concerns persist. Entrepreneurs leveraging the metaverse tend to adopt business models that include virtual real estate development, NFTs (non-fungible tokens), and immersive experiences. In conclusion, the metaverse presents significant business opportunities, but entrepreneurs must navigate various challenges related to technology, market dynamics, and consumer behavior.